GLOBALIZATION EFFECT ON PANCASILA VALUES APPLICATION AMONG MILLENNIAL GENERATION - Umi Sofiana; Moses glorino Rumambo pandin (Jurnal Global Citizen : Jurnal Ilmiah Kajian Pendidikan Kewarganegaraan, 2021)
Pancasila is taken from the noble values that exist and are well-grown in the life of Indonesian society. It shows that the position of Pancasila itself is the source of all sources of law. This research aims to find out the effect of Pancasila values on the attitudes of the younger generations attitude in this era. Whether the changing period can cause the understanding of Pancasila values has changed during the current development, and it affecting the millennial lifestyle and attitude. This study uses a literature review method by collecting and analyzing articles related to the effect of understanding the values of Pancasila on the millennial generation. The article criteria that will be used are articles published in the year 2019-2021. Based on the article that has been collected, it is found that a person’s understanding of the values of Pancasila dramatically affects the way a person behaves. The more a person understands the values contained in Pancasila, the attitudes and lifestyle shown reflect the good Indonesian culture as taught by ancestors and religion. On the other hand, if the understanding is lacking, someone will tend to be more open to habits from foreign cultures that do not match our ancestors’ teachings.